the Risk Factors for the Incidence of Obesity in Students at STIKes Hang Tuah Pekanbaru 2020: Faktor Risiko Kejadian Obesitas Pada Mahasiwa Di STIKes Hang Tuah Pekanbaru tahun 2020 - Guntur Pamungkas Pamungkas; Christine Vita GP; Agus Alamsyah (Jurnal Kesehatan Komunitas, 2021)
Obesity is an excessive accumulation of body fat that can pose a health risk to individuals such as type 1 or 2 diabetes, high blood pressure, stroke, heart attack, heart failure, cancer, and other diseases caused by obesity. Obesity is still a serious health problem, Indonesia has obese people as much as 31.0% while for Riau Province obese people as much as 33.5%. Pekanbaru city ranks 11th in Riau Province with 1,880 or 36.35% obese people and for STIKes Hang Tuah Pekanbaru, students with obesity for the year 2018 as much as 170 or 24.0%. The purpose of this study is to determine the risk factors of obesity incidence in students at STIKes Hang Tuah Pekanbaru Year 2020. This was an quantitative study with analytical design and cross-sectional approach. The research was conducted at STIKes Hang Tuah Pekanbaru in July-August 2020. The study sample was 154 respondents. The sampling technique was used purposive sampling by the grouping of the study program. Data analysis includes uni-variate and bi-variate analysis, using chi-square tests. The results of the uni-variate analysis showed low knowledge variables (49.4%), less sleep duration (45.5%), less physical activity (55.8%), poor diet (40.3%). The results of bi-variate analysis showed variables related to obesity incidence in students namely knowledge (p-value = 0.000, POR = 19,697), sleep duration (p-value = 0.000, POR = 4,362), physical activity (p-value = 0.000, POR = 4.006), diet (p-value = 0.003, POR = 0.353). Keywords : Physical Activity, Sleep Duration, Obesity, Knowledge